2022
DOI: 10.1186/s12974-022-02439-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic landscape subtype and clinical prognosis of patients with the cognitive impairment by Japanese encephalitis infection

Abstract: Background Cognitive impairment is one of the primary sequelae affecting the quality of life of patients with Japanese encephalitis (JE). The clinical treatment is mainly focused on life support, lacking of targeted treatment strategy. Methods A cerebrospinal fluid (CSF) proteomic profiling study was performed including 26 patients with JE in Gansu province of China from June 2017 to October 2018 and 33 other concurrent hospitalized patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Changes in WBC in CSF and total protein in blood are commonly associated with viral infections. The significant changes in N% and L% are consistent with a previous proteomics study, which reported decreased levels of L%, M%, and increased levels of complement components as potential clinical markers for poor prognosis in JE ( 7 ). The statistical analysis based on mRS results further validated the significant changes in N% and L% in blood as indicators for the prognosis of JE.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Changes in WBC in CSF and total protein in blood are commonly associated with viral infections. The significant changes in N% and L% are consistent with a previous proteomics study, which reported decreased levels of L%, M%, and increased levels of complement components as potential clinical markers for poor prognosis in JE ( 7 ). The statistical analysis based on mRS results further validated the significant changes in N% and L% in blood as indicators for the prognosis of JE.…”
Section: Resultssupporting
confidence: 91%
“…However, the major risk factors contributing to poor prognosis in JE infections remain unclear. Our previous research focused on analyzing proteome profiling changes in the cerebrospinal fluid (CSF) of severe adult JE patients, identifying a subgroup with lower survival rates and a higher risk of cognitive impairment ( 7 ). Identifying key factors associated with poor prognosis through clinical indicators is an ongoing research topic in JE.…”
Section: Introductionmentioning
confidence: 99%
“…To date, to our knowledge, two studies have utilized unbiased techniques to examine the CSF proteome in human patients with confirmed JEV infection; while they demonstrate the feasibility of the methods, the patients were not confirmed by seroneutralization and included relatively small numbers of patients (10 and 26 JE patients). , There have been a handful of studies utilizing ELISA methods to target specific proteins; however, these rarely used power calculations in their experimental design, nor did they include adequate controls. Analysis of the transcriptome and proteome in animal models and cell culture ,, have been performed; however, the comparability to human CSF and comparison with other neurological infections is limited. Furthermore, mRNA expression does not directly correlate with that of the corresponding protein …”
Section: Discussionmentioning
confidence: 99%
“…This will inform the use of a smaller subset of proteins in an ELISA or rapid diagnostic test (RDT) to be tested alongside the existing anti-JEV IgM assay. To date, to our knowledge, two studies have utilized unbiased techniques to examine the CSF proteome in human patients with confirmed JEV infection; while they demonstrates the feasibility of the methods, the patients were not confirmed by seroneutralisation and included relatively small numbers of patients (10 and 26 JE patients) (46,47). There have been a handful of studies utilizing ELISA methods to target specific proteins, however these rarely used power calculations in their experimental design, nor did they include adequate controls (48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%